Creating Justice in Society According to Buddhist Ethics - Saengool, Komgris; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic article aims to present in creating social justice according to Buddhist ethics, it was found that justice could be achieved by having love or compassion as the basis for expressing goodwill to one another, leading to peace in society. In addition, the love of people in this society will lead to the reduction of inequality in all aspects, thereby creating justice in society.